Pulmonary Metastasis of a Prostate Adenocarcinoma within a Primary Lung Adenocarcinoma: A Tumor-totumor Metastasis Case Report - Ribeiro, André Marcondes Braga; Vivan, Ana Luiza Tatarin; Lima, Eduardo Nóbrega Pereira; Formiga, Maria Nirvana da Cruz; Donadio, Mauro Daniel Spina; Costa, Felipe D'Almeida (Brazilian Journal of Oncology, 2019)
Applications for68 Ga-PSMA PET-CT continue to expand beyond prostate cancer. The objective of this case report is to illustrate a rare phenomenon known as tumor-totumor metastasis in which precise histological diagnosis is an essential prerequisite for correct clinical management of patients. A 89-year-old man with prostate cancer underwent68 Ga-PSMA PET-CT study for rescreening after increasing prostate specific antigen (PSA), revealing abnormal uptake of the radioindicator in the prostate and bilateral lung nodules. A biopsy was performed on one of the left lung nodules and the results of the pathology examination revealed that the lesion consisted of metastatic prostatic adenocarcinoma within a primary lung adenocarcinoma.
Keywords: Neoplasm Metastasis; PROSTATE; LUNG.